COPING MECHANISMS OF STUDENTS FROM BROKEN HOMES IN ISLAMIC RELIGIOUS EDUCATION - Sujai, Ahmad; Arifin, Mohamad Zaenal; Amalia, Neneng (Edukasi Islami: Jurnal Pendidikan Islam, 2025)
Background: This research is motivated by the growing concern over the psychological challenges faced by students from broken home families and the role of education in mitigating these challenges. Purpose: This study explores the role of Islamic Religious Education (IRE) teachers in helping students from broken home families develop coping mechanisms. It investigates the problems and psychological impacts faced by these students and the methods used by IRE teachers to support them. Method: This qualitative case study involves five IRE teachers and five students with broken home backgrounds from Al Fattah Junior High School in Tangerang Regency. Data were collected through observations, interviews, and documentation. Result: The study finds that broken home situations, including parental divorce, economic difficulties, communication breakdowns, and neglect, lead to negative impacts on students' behavior and well-being. However, IRE teachers help students cope by fostering positive thinking, self-control, patience, and a sense of resilience through prayer, dhikr, and sincerity. Conclusion: The findings highlight the significant influence of IRE teachers in guiding these students toward emotional regulation, optimism, and a positive outlook on life, thereby improving their academic engagement and personal development.